Neurochemical properties of BDNF-containing neurons projecting to rostral ventromedial medulla in the ventrolateral periaqueductal gray - Yin, Jun-Bin; Wu, Huang-Hui; Dong, Yu-Lin; Zhang, Ting; Wang, Jian; Zhang, Yong; Wei, Yan-Yan; Lu, Ya-Cheng; Wu, Sheng-Xi; Wang, Wen; Li, Yun-Qing (Frontiers in Neural Circuits, 2014)
The periaqueductal gray (PAG) modulates nociception via a descending pathway that relays in the rostral ventromedial medulla (RVM) and terminates in the spinal cord. Previous behavioral pharmacology and electrophysiological evidence suggests that brain-derived neurotrophic factor (BDNF) plays an important role in descending pain modulation, likely through the PAG-RVM pathway. However, there still lacks detailed information on the distribution of BDNF, activation of BDNF-containing neurons projecting to RVM in the condition of pain, and neurochemical properties of these neurons within the PAG. Through fluorescent in situ hybridization (FISH) and immunofluorescent staining, the homogenous distributions of BDNF mRNA and protein were observed in the four subregions of PAG. Both neurons and astrocytes expressed BDNF, but not microglias. By combining retrograde tracing methods and formalin pain model, there were more BDNF-containing neurons projecting to RVM being activated in the ventrolateral PAG (vlPAG) than other subregions of PAG. The neurochemical properties of BDNF-containing projection neurons in the vlPAG were investigated. BDNF-containing projection neurons expressed auto receptor Tropomyosin-related kinase B (TrkB) in addition to serotonin (5-HT), neurotensin (NT), substance P (SP), calcitonin gene related peptide (CGRP), nitric oxide synthase (NOS), and parvalbumin (PV) but not tyrosine decarboxylase (TH). It is speculated that BDNF released from projection neurons in the vlPAG might participate in the descending pain modulation through enhancing the presynaptic release of other neuroactive substances (NSs) in the RVM.